2018
DOI: 10.3390/w10080980
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Characteristics of Organic Matter and Nutrients Released from Sediments into Agricultural Reservoirs

Abstract: Most agricultural reservoirs in Korea are more than 50 years old, have low water depth and storage capacity, and have experienced contaminant deposition for decades. Contaminated sedimentation on the reservoir bottom can cause water pollution and eutrophication. Consequently, intervention is required to remove and manage the sediments. We analyzed the release characteristics of organic matter and nutrients from sediments of four reservoirs to predict the pollution caused by sediment release and investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This transition coincided with the socioeconomic movement in Korea that commenced from the 1960s, during which fertilizers, livestock, sewage, pesticides, and modern farming equipment were broadly disseminated (Park 2003). The overall ranges of TP are similar to those observed in other agricultural reservoirs in western Korea, where sediments were contaminated by sewage and livestock (e.g., Lee and Oh 2018).…”
Section: Vegetation and Water Level Changesupporting
confidence: 80%
“…This transition coincided with the socioeconomic movement in Korea that commenced from the 1960s, during which fertilizers, livestock, sewage, pesticides, and modern farming equipment were broadly disseminated (Park 2003). The overall ranges of TP are similar to those observed in other agricultural reservoirs in western Korea, where sediments were contaminated by sewage and livestock (e.g., Lee and Oh 2018).…”
Section: Vegetation and Water Level Changesupporting
confidence: 80%
“…Thus, Brito et al [27] concluded that decreasing loads to these levels would require: (i) reducing the suspended material inflow to the reservoir especially during flash flood, which would mean placing retention barriers upstream to retain sediment, preserving riparian vegetation and promoting conservation tillage practices in the catchment, in line with ARH Alentejo [18] and Ramos et al [21]; and (ii) removing anoxia from the reservoir bottom through O 2 aeration at the reservoir bottom. This later solution was also proposed by Lee and Oh [9] for South Korean reservoirs, with these requiring aeration in the bottom when anoxic conditions were present. These authors further suggested that for reservoirs subjected to livestock pollution sources, priority should be given to sediment management, namely by seasonally supplying O 2 to the bottom of the reservoirs to control the release rate of contaminants from sediment.…”
Section: Responsementioning
confidence: 95%
“…Those authors inferred that the internal P release contributing to a reservoir's high trophic level could last for several decades, even when external loading was reduced. Likewise, Lee and Oh [9] referred that the sediment release fluxes were considerable compared to loads from the catchment, highlighting the need for reducing the internal pollutant loads in four reservoirs in South Korea.…”
Section: Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sediment composition is also modified by land use in the adjacent catchment area (Haddadchi & Hicks, 2019), especially when this is arable land (causing surface runoff of fertilizers and plant protection products rich in nutrients; Ferreira et al, 2020;Lee & Oh, 2018), as well as industrial sites (Hayzoun et al, 2014), landfills (Zinabu et al, 2019), and sewage treatment plants (sources of specific organic pollutants as well as heavy metals) (Loizeau et al, 2004;B. Wu et al, 2014).…”
mentioning
confidence: 99%